Strategi Peningkatan Kemampuan Komunikasi Matematis Siswa SD/MI - Dessy Noor Ariani (Fakultas Studi Islam UNISKA MAB Banjarmasin, 2017)
IndonesiaPendahuluan: Artikel ini bertujuan untuk menjelaskan pengertian kemampuan komunikasi matematis siswa, peran guru dalam meningkatkan kemampuan komunikasi matematis siswa SD/MI, bentuk soal matematika untuk meningkatkan komunikasi matematis siswa SD/MI, dan strategi pembelajaran yang dapat digunakan dalam meningkatkan komunikasi matematis siswa SD/MI. Metode: Tulisan ini merupakan kajian pustaka tentang strategi meningkatkan kemampuan komunikasi matematis siswa SD/MI. Hasil: 1) Kemampuan komunikasi matematika adalah kemampuan dalam menyampaikan ide matematika, baik secara lisan maupun tulisan serta kemampuan memahami dan menerima ide matematika orang lain secara cermat, analisis, kritis, dan evaluatif untuk mempertajam pemahaman; 2) Peran guru dalam mengembangkan komunikasi matematis siswa SD/MI meliputi: a) merancang pembelajaran yang dapat meningkatkan intensitas interaksi guru dengan siswa dan antar siswa, b) memberikan motivasi kepada siswa, c) menyeleksi tugas-tugas yang akan diberikan, dan d) mengukur kemampuan matematis siswa dengan pemberian soal uraian; 4) Strategi pembelajaran untuk meningkatkan kemampuan komunikasi matematika siswa SD/MI adalah: a) Strategi pembelajaran kooperatif tipe think-talk-write; b) Strategi pembelajaran interaktif; c) Strategi pembelajaran Kooperatif Tipe Teams-Games-Tour-Tournaments; d) Pendekatan pendidikan matematika realistik (PMR); dan e) Pendekatan pembelajaran Problem Based Learning (PBL). EnglishIntroduction: The purposes of this article are to explain understanding of students’ mathematical communication skills, the teachers’ role to improve students' mathematical communication skills in elementary school, design of mathematical question form to improve mathematical communication in elementary school, the strategies to improve mathematical communication skill in elementary school. Method: This paper is library research to know strategies improving mathematical communication skill in elementary school. Results: 1) The mathematical communication skill is the ability to present mathematical ideas, both orally and in writing and the ability to understand and accept other people's mathematical ideas carefully, analytically, critically and evaluatively for building mathematical knowledge; 2) The teachers’ role in developing mathematical communication of elementary students are: a) designing methods, approaches, and strategies that increase the intensity of teacher interaction with students and among students, b) giving motivation to students, c) selecting the tasks, and d) measuring students' mathematical communication ability by giving essay task; 5) Strategies to improve mathematical communication skills in elementary school are: a) cooperative learning strategy type think-talk-write; b) interactive learning strategy; c) Cooperative Teams-Games-Tour-Tournaments Cooperative Learning Strategy; d) Realistic mathematics education (RME) approach; and e) Problem Based Learning (PBL) approach.